Conservative medical intervention as a complement to CDT for BCRL therapy: a systematic review and meta-analysis of randomized controlled trials - Deng, Chuyu; Wu, Zhiguo; Cai, Zijie; Zheng, Xiaoyan; Tang, Chunzhi (Frontiers in Oncology, 2024)
Background The effect of first-line complex decongestive therapy (CDT) for breast cancer-related lymphedema (BCRL) depending on various factors forces patients to seek additional treatment. Therefore, this meta-analysis was conducted to evaluate the effect of different conservative medical interventions as a complement to CDT. This is the first meta-analysis that includes various kinds of conservative treatments as adjunctive therapy to get broader knowledge and improve practical application value, which can provide recommendations to further improve BCRL patients’ health status. Methods RCTs published before 18 December 2023 from PubMed, Embase, Cochrane Library, and Web of Science databases were searched. RCTs that compared the effects of conservative medical intervention were included. A random-effects or fixed-effects model was used based on the heterogeneity findings. Study quality was evaluated using the Cochrane risk of bias tool. Results Sixteen RCTs with 690 participants were included, comparing laser therapy, intermittent pneumatic compression (IPC), extracorporeal shock wave therapy (ESWT), electrotherapy, ultrasound, diet or diet in combination with synbiotic supplement, traditional Chinese medicine (TCM), continuous passive motion (CPM), and negative pressure massage treatment (NMPT). The results revealed that conservative medical intervention as complement to CDT had benefits in improving lymphedema in volume/circumference of the upper extremity [SMD = −0.30, 95% CI = (−0.45, −0.15), P < 0.05, I2 = 51%], visual analog score (VAS) for pain [SMD = −3.35, 95% CI (−5.37, −1.33), P < 0.05, I2 = 96%], quality of life [SMD = 0.44, 95% CI (0.19, 0.69), P < 0.05, I2 = 0], and DASH/QuickDASH [SMD = −0.42, 95% CI (−0.70, −0.14), P < 0.05, I2 = 10%] compared with the control group. Subgroup analysis revealed that laser therapy and electrotherapy are especially effective (P < 0.05). Conclusion Combining conservative medical interventions with CDT appears to have a positive effect on certain BCRL symptoms, especially laser therapy and electrotherapy. It showed a better effect on patients under 60 years old, and laser therapy of low to moderate intensity (5–24 mW, 1.5–2 J/cm2) and of moderate- to long-term duration (≥36–72 sessions) showed better effects. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=354824, identifier CRD42022354824.